2018
DOI: 10.1186/s12879-018-3459-0
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in tuberculosis infection control practice via technical support in two regions of Ethiopia

Abstract: BackgroundGlobally recommended measures for comprehensive tuberculosis (TB) infection control (IC) are inadequately practiced in most health care facilities in Ethiopia. The aim of this study was to assess the extent of implementation of TB IC measures before and after introducing a comprehensive technical support package in two regions of Ethiopia.MethodsWe used a quasi-experimental design, whereby a baseline assessment of TB IC practices in 719 health care facilities was conducted between August and October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
(21 reference statements)
1
10
1
Order By: Relevance
“…Other studies support the finding that HCWs have a high incidence and prevalence of TB [18][19][20]. The yield of TB among the HCWs in this study is even higher than the studies in China [18,19].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Other studies support the finding that HCWs have a high incidence and prevalence of TB [18][19][20]. The yield of TB among the HCWs in this study is even higher than the studies in China [18,19].…”
Section: Discussionsupporting
confidence: 83%
“…The yield of TB among the HCWs in this study is even higher than the studies in China [18,19]. This might be due to poor TB infection control at health facilities in Ethiopia [20]. Similarly, a systematic review in low-and middle-income countries indicated that the incidence rate of TB among HCWs is 2.94 times higher (95% CI, 1.67-5.19) than in the general population [21].…”
Section: Discussioncontrasting
confidence: 66%
“…8 In low/ middle-income countries (LMICs), where TB incidence is high, 1 implementation of TB infection prevention and control (IPC) measures to reduce the risk of transmission of TB infection in health facilities is consistently reported to be poor. [9][10][11][12] Poor healthcare provider knowledge and motivation as well as poor infrastructure and personal respiratory protection supplies are common explanations provided for suboptimal implementation. 9 10 13-17 The WHO published the latest iteration of TB-specific guidelines for the prevention and control of transmission of TB infection in health facilities in 2019.…”
Section: What Do the New Findings Imply?mentioning
confidence: 99%
“…Training and political commitment are crucial to efforts to ensure HCW safety. The International Council of Nurses, the US Agency for International Development (USAID), US CDC, WHO, Harvard/Partners in Health, and other non-governmental organizations such as the Union, PATH, Services for Health in Asian African Regions (SHARE), International Center for AIDS Care and Treatment Programs (ICAP), Project Hope, Stop TB Partnership, and the Royal Dutch Anti-TB Foundation (KNCV) have been engaged in promising initiatives in countries of the former Soviet Bloc (including Latvia, the Russian Federation, and Tajikistan), Latin America (Peru), sub-Saharan Africa (South Africa and Malawi), India, and China (88)(89)(90)(91)(92)(93)(94)(95). Over the past two decades, the authors have had the opportunity and privilege to help develop and work with highly successful Centers of Excellence in Riga, Latvia; Vladimir, Russian Federation; and Dushanbe, Tajikistan.…”
Section: Healthcare-associated Infections Healthcare Workers and Infection Prevention And Controlmentioning
confidence: 99%